“…Given to Comrade V.V. Mayakovsky”: An Unknown Letter by Lunacharsky to Dzerzhinsky - Vera N. Terekhina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The article presents the historical context of the first-published document from the GARF foundations — A.V. Lunacharsky's letter of recommendation about V.V. Mayakovsky, addressed to F.E. Dzerzhinsky on April 13, 1918. In this regard, Mayakovsky was recommended to Dzerzhinsky as well-in knowledge of “artists, poets and other actors, in one way or another associated with anarchist groups”, for their “rehabilitation and termination of persecution”. The article establishes a link between the two events related to the published letter, namely, the release of the first and only issue of “Futurist Newspaper” on March 15 and the closing of “Cafe of Poets” on April 14, 1918. Based on the published letter, the article establishes a connection between the two events, namely, the release of the first and only issue of “Futurist Newspapers” on March 15 and the closing of “Cafe of Poets” on April 14, 1918. It concludes that there is a need for an in-depth examination of the anarchist period in Mayakovsky's creative biography. In this context, Lunacharsky's letter of recommendation to Dzerzhinsky is the earliest official document of Mayakovsky’s soviet period.